The role of selected chemokines and their receptors in the pathogenesis and destabilisation of atheromatous plaques in the carotid arteries - Maria Konarska-Król; Magdalena Justyna Kacperska; Jakub Walenczak; Bartłomiej Tomasik; Piotr Szpakowski (Aktualności Neurologiczne, 2015)
Chemokines are cytokines that act selectively on cells and are capable of inducing selective migration of cells in vitro and in vivo. The term was first coined at the 3rd International Symposium on Chemotactic Cytokines in 1992. The name “chemokine” is a contraction of “chemotactic cytokine,” meaning that these molecules combine features of both cytokines and chemotactic factors. They are a family of low-molecular-mass proteins acting on specific membrane receptors. A cell’s overall sensitivity to chemotaxis depends on the expression profile of chemokine receptors. Atherosclerosis is essentially an excessive inflammatory and proliferative response to the damage of arterial walls. It takes place within the wall and leads to the formation of unstable atherosclerotic plaques. Many chemokines have been studied in terms of their role in the pathogenesis of an atheromatous plaque in the carotid arteries, both in animal models and with the use of human tissue. It  seems that molecules that are the most involved in the formation of atheromas in the carotid arteries include: CCL2, CCL3, CCL4 and CCL5. However, reports are sometimes contradictory, and more research is needed. Finding a marker that could help predict the destabilisation of an atheromatous plaque would be a valuable addition to the standard diagnostic panel of tests used in both the diagnosis and monitoring of vascular pathologies.